Pineapple Waste Commercialisation - Aizi Nor Mazila, Ramli (2020)
Pineapple, also known by its scientific name Ananas comosus, is a type of tropical plant commonly planted in Malaysia, specifically in Johor. Now, the nation’s pineapple plantations have expanded rapidly to other states such as Selangor, Pahang, Sarawak, Perak, and Kedah.